2017
DOI: 10.1124/jpet.117.245522
|View full text |Cite|
|
Sign up to set email alerts
|

Selective Cannabinoid 2 Receptor Stimulation Reduces Tubular Epithelial Cell Damage after Renal Ischemia-Reperfusion Injury

Abstract: Ischemia-reperfusion injury (IRI) is a common cause of acute kidney injury (AKI), which is an increasing problem in the clinic and has been associated with elevated rates of mortality. Therapies to treat AKI are currently not available, so identification of new targets that can be modulated to ameliorate renal damage upon diagnosis of AKI is essential. In this study, a novel cannabinoid receptor 2 (CB2) agonist, SMM-295 [3'-methyl-4-(2-(thiophen-2-yl)propan-2-yl)biphenyl-2,6-diol], was designed, synthesized, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 73 publications
2
20
0
2
Order By: Relevance
“…The CB2 docking was done only for those molecules that were not selective in the CB1 and CB2 radioligand-binding assay. The CB2 receptor grid was prepared by choosing the centroid of residues Lys109 3.28 , Ser112 3.31 , Phe117 3.36 , Trp194 5.43 , Trp258 6.48 , Lys278, and Ser285 7.39 as reported in our previous publication [ 29 ], and the docking was carried out with the same protocol as for the CB1 model. In the XP docking, no constraint was applied for CB2 receptor docking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CB2 docking was done only for those molecules that were not selective in the CB1 and CB2 radioligand-binding assay. The CB2 receptor grid was prepared by choosing the centroid of residues Lys109 3.28 , Ser112 3.31 , Phe117 3.36 , Trp194 5.43 , Trp258 6.48 , Lys278, and Ser285 7.39 as reported in our previous publication [ 29 ], and the docking was carried out with the same protocol as for the CB1 model. In the XP docking, no constraint was applied for CB2 receptor docking.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is being used by several researchers who have shown that peripherally restricted CB1 antagonists and inverse agonists reduce body weight and improve metabolic profile in vivo, while being devoid of CNS-mediated side effects [ 23 , 24 ]. On the other hand, the CB2 receptor is also an important target for the discovery of therapeutics for neuro-inflammation, cardiometabolic disorder, cardiac ischemia, renal ischemia–reperfusion injury, and other diseases/disorders [ 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the pathological state, excessive free radicals produced in the body cause oxidative damage to kidney tissues, leading to the formation of diseases, such as kidney stones [22]. TPSs have good antioxidant capacity, and TPS treatment can improve the ability of renal epithelial cells to resist oxidative damage [23,24]. The results showed that TPSs protected HK-2 cells from damage caused by nano-COM crystals by reducing ROS production.…”
Section: Reduction Of Cytotoxicity Of Com Crystals Aftermentioning
confidence: 99%
“…İ/R çalışmasında akciğer dokusundaki miyeloperoksidaz aktivasyonu, şam kontrol grubu ile İ/R grubu arasında karşılaştırma yapılması sonucu akciğer dokusunda evans miktarının kontrol grubuna göre daha fazla olduğu bulunmuştur. Aynı zamanda CB2 agonisti ile karaciğer dokusunda ve diğer dokularda İ/R hasarına karşı koruyucu özelliğe sahip olduğu bilimsel çalışmalar sonucu bulunmuştur (19)(20)(21). Astım sonucu solunum yollarında meydana gelen bozulmanın önemli bir etkisi akciğer dokusunda plazma proteinlerinin kılcal damardan sızmasıdır.…”
Section: Materyal Ve Metodunclassified
“…Kanabidiol, bağışıklık sisteminde etkili olan TNFα ve nitrik oksit derecesini önemli ölçüde düzenlemiştir (23). Kanabinoidlerin yapısal özelliklerinden dolayı doku hasarına karşı koruyucu ilaç gibi kullanılabilir (20,22).…”
Section: Materyal Ve Metodunclassified